PENGARUH REFORMASI ADMINISTRASI PERPAJAKAN TERHADAP KINERJA FISKUS (Studi pada Fiskus (Pegawai Pajak) KPP Pratama Batu) - Fadhilah, Moch. Fatkur (Jurnal Mahasiswa Perpajakan, 2014)
The study examined the relationship between tax reform represented by the structure variable (X1), Procedures (X2), Strategy (X3), Culture (X4) on the performance of the tax authorities (tax officials). This research is a quantitative research throught Â survey or questionnaire approach. Methods of data analysis using multiple linear regression analysis. Data retrieved by using non probabilty sampling with quota sampling approach, to obtain a sample of 57 respondents. Based on these studies it is known that the performance of the tax authorities is influenced by the structure and procedures of the organization, while the organization's strategy and culture did not affect significantly. In testing it was found that organizational strategies are still centralisasi strategy, the strategy derived from the central office, KPP Pratama Batu can not implement its own strategy to collect taxes in the Batu city. the existence of the diverse interests of organizational culture in public organizations, in turn, affects public organizations in terms of type of activity, funding strategies, and the implementation or execution of activities. It also affects the organizational culture, where public organizations are KPP Pratama Batu could not develop an organizational culture that is solely focused on direct user or customer. Keyword : Taxation, Structure Organization, Procedure Organization, Strategy Organization, Culture Organization, Performance of Tax Authorities